PENDAPATAN ASLI DAERAH SEKTOR KEHUTANAN PADA ERA OTONOMI DAERAH DI KABUPATEN MUNA - A. Mujetahid (Forestry Faculty of Universitas Hasanuddin, 2012)
This research was aimed to know contribution of forestry sector to Local Government Revenue at district of Muna in regional autonomy era. The research result is expected to contribute in evaluating and compiling Regional Budget and Expenditure Plan. The result is also intended as an evaluation of forest product restribution policy. Data were collected with purpossive sampling using observation technique/survey, interview and discussion with related stakeholders. The data was then processed, tabulated, clasified base on with research aim, and analysed descriptively. The results show that the contribution of forestry sector to Local Government Revenue to Muna district during 2000-2004 in average was 36.77% of Local Government Revenue in total. Key words: contribution, forestry sector, Local Government Revenue, regional autonomy